Routes of technological exploitation of agricultural waste for power generation - Batista, Renato Rocha; Bacelos, Marcelo S; Chaves, Gisele de Lorena Diniz; Lira, Taisa S; Arrieche, Leonardo (Latin American Journal of Energy Research, 2021)
Abstract: The use of agricultural residues as a bioenergy source has aroused increasing interest in the bioenergy sector. This paper discusses the exploitation of cocoa and coffee husks using anaerobic digestion, pyrolysis and direct combustion technologies. The structural synthesis method that was used to obtain electricity was performed using a State Tree. Structural elements were combined to form branches for each chemical route. Structural optimisation was conducted using the heuristic method. The promising technological routes included the anaerobic digestion of cocoa husks in a batch reactor and the pyrolysis of coffee husks preceded by pelletisation. The systematic representation of the problem using the process engineering approach was a promising method for evaluating the process of obtaining energy from fruit wastes.